Efektivitas Senam Ritmik Pada Perkembangan Motorik Kasar Anak Usia Dini Di Ra Al-Junaidiyah - Zulpina Zulpina; Sopia Wulandari; Rizkiyah Nur Lubis; Nada Riani; Muhammad Randi (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
Early childhood is an individual who is undergoing a rapid development process, so preschool children need optimization of gross motor development by using rhythmic gymnastics. This study aims to improve the gross motor skills of children aged 4-6 years at RA Al-Junaidiah. The problem in this study is to see how effective rhythmic gymnastics is on the gross motor development of children aged 4-6 years at RA Al-Junaidiah. The data collection technique in this study used the Participation Action Research (PAR) method. Based on the results of the study, it can be seen that rhythmic gymnastics can improve children's gross motor skills at RA Al-Junaidiah. Thus the conclusion of this study is that there is a significant effect of rhythmic gymnastics on children's gross motor development at RA Al-Junaidiah.